Prevalence and impact of molecular variation in the three-prime repair exonuclease 1 TREX1 and its implications for oncology - Marwa Shekfeh; Mariam M. Konaté; Julia Krushkal (Human Genomics)
Abstract Background The three-prime repair exonuclease 1, TREX1, degrades cytosolic DNA to prevent aberrant immune activation. Its inactivation results in DNA accumulation in the cytosol and induction of the cGAS-STING DNA sensing pathway, interferon signaling, and inflammation. Germline pathogenic TREX1 mutations are known to lead to hereditary autoimmune and autoinflammatory disorders, whereas the consequences of TREX1 mutations in cancer remain poorly understood. Results To assess the importance of human TREX1 amino acid variants, we analyzed protein sequences of the functional TREX1b isoform from 168 mammalian species and integrated available data on TREX1 sequence and copy number alterations in hereditary autoimmune and autoinflammatory disorders, cancer, and in human populations. While the entire TREX1b protein was conserved in placental mammals, egg-laying mammals and marsupials had their own unique C-terminal regions, with each predicted to contain a transmembrane domain. We modeled human TREX1 variants occurring in autoimmune disease and cancer samples at 12 protein positions to evaluate their predicted impact on protein stability and function. Conclusions Our findings provide novel insight into the role of TREX1 molecular variation in cancer, where genetic or epigenetic loss of TREX1 activity may improve susceptibility to treatment. However, TREX1 gene deletion in tumors was associated with unfavorable patient outcomes, most likely due its frequent co-occurrence with the loss of the entire 3p chromosomal arm, which contains known cancer-related genes.